Combining hydro-acoustic sources and bathymetric differences to track the vent evolution of the Mayotte eruption, Mozambique Channel - Saurel, Jean-Marie; Retailleau, Lise; Deplus, Christine; Loubrieu, Benoît; Pierre, Delphine; Frangieh, Michel; Khelifi, Nassim; Bonnet, Robin; Ferrazzini, Valérie; Bazin, Sara; Guyavarch, Pierre; Moulin, Maryline; et al. (Frontiers in Earth Science, 2022)
The majority of Earth volcanism takes place in the deep ocean. Deep-sea volcanoes are particularly complicated to study due to their remoteness. Very different methods can be used and their combination can lead to crucial information about submarine volcanoes behavior. In Mayotte, Comoros archipelago, efforts have been made to study and monitor the volcanic activity currently occurring east of Mayotte through various methods and campaigns on land and at sea. In October 2020, a line of 10 Ocean Bottom Seismometers was deployed during 10 days, leading to a hand-picked catalog of more than a thousand of hydro-acoustic signals, which have been associated with reactions between hot lava and deep cold ocean waters. During the same period, repeated swath bathymetry surveys were performed over an active lava flow field. We compare the time evolution of the hydro-acoustic events locations and bathymetry differences observed between each survey. While bathymetric information gives absolute location of new lava flows, hydro-acoustic events give detailed relative time variations leading to short-term spatial evolution. Bathymetric information thus provides snapshots of the eruptive area evolution at specific times, when hydro-acoustic signals show its continuous evolution. By combining both analyses we are able to clearly define the detailed evolution of the lava flows pattern in the short time period of ten days. Applied to the data already acquired on Mayotte since 2019, this method could allow us to estimate more precisely the volcano effusion rate and its evolution, giving further insights on the feeding system.